Metabolic profiling of elite athletes with different cardiovascular demand. (29th April 2019) - Al‐Khelaifi, Fatima; Donati, Francesco; Botrè, Francesco; Latiff, Aishah; Abraham, David; Hingorani, Aroon; Georgakopoulos, Costas; Suhre, Karsten; Yousri, Noha A.; Elrayess, Mohamed A.
Abstract : Intensive exercise of elite athletes can lead to physiological alterations in the cardiovascular system in response to increased stroke volume and blood pressure, known collectively as cardiovascular demand (CD). This study aimed to compare metabolic differences in elite athletes with high vs low/moderate CD and to reveal their underlying metabolic pathways as potential biomarker signatures for assessing health, performance, and recovery of elite athletes. Metabolic profiling of serum samples from 495 elite athletes from different sport disciplines (118 high CD and 377 low/moderate CD athletes) was conducted using non‐targeted metabolomics‐based mass spectroscopy combined with ultra‐high‐performance liquid chromatography. Results show that DAGs containing arachidonic were enriched in high CD together with branched‐chain amino acids, plasminogens, phosphatidylcholines, and phosphatidylethanolamines, potentially indicating increased risk of cardiovascular disease in the high CD group. Gamma‐glutamyl amino acids and glutathione metabolism were increased in low/moderate CD group, suggesting more efficient oxidative stress scavenging mechanisms than the high CD group. This first most comprehensive metabolic profiling of elite athletes provides an evidence that athletes with different CD show a unique metabolic signature that reflects energy generation and oxidative stress and potentially places the high CD group at a higher risk of cardiovascular disease. Further studies are warranted for confirmation and validation of findings in other sport groups in light of potential confounders related to limited available information about participants.